2019–2020 Florida Citrus Production Guide: Postbloom Fruit Drop - Natalia A. Peres; Megan M. Dewdney (EDIS)
Postbloom fruit drop (PFD) must be controlled on processing and fresh-market fruit. PFD, caused by the fungus Colletotrichum acutatum, affects all species and cultivars of citrus, but severity on a given cultivar varies according to the time of bloom in relation to rainfall. Navel and Valencia oranges have experienced the most severe damage in Florida since they tend to have extended or multiple blooms. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Natalia A. Peres and Megan M. Dewdney, and published by the Plant Pathology Department, March 2019.